Slavery, freedom and conflict : a story of two Birminghams - Bownas, Jane L. (Sussex Academic Press, 2020)
A Story of Two Birminghams examines the roles played by two cities and the areas in which they are situated in the long history of people of African origin and their ancestors who were taken into slavery, experienced a phoney freedom and subsequently experienced racism, segregation and violence. From the eighteenth century the industrial city of Birmingham in England was involved in the manufacture of guns used in the African slave trade and then later, in the production and export of the steam engines used on the sugar plantations in the West Indies. In northern Alabama, on land where another industrial city of the same name would later develop, African slaves worked on cotton plantations owned by planters who would later make their fortunes by selling the mineral rich land. Abolitionists in Birmingham UK, and in the Southern States fought against much opposition to achieve freedom for the slaves. But this was often a phoney freedom: for example, under an 'apprenticeship' system in Jamaica people endured conditions often worse than under slavery, and in Alabama they endured hard labour in the development of the new industrial city and under the 'Convict Lease 'system. Slavery, Freedom and Conflict follows the life path of descendants of slaves into the twentieth century, the difficulties experienced by West Indian immigrants in Birmingham UK, the segregation laws imposed in Birmingham, Alabama and the US Civil Rights movement which followed. Later in the century, riots occurring in Handsworth (Birmingham UK), the election of a far-right, racist politician in nearby Smethwick and the infamous speech of Enoch Powell indicated that, as in Birmingham, Alabama many black people were still suffering from the iniquities of the slave trade inflicted upon their ancestors more than two hundred years previously. This book is essential reading for all those with an interest in the history of slavery, and in the local history of the West Midlands of England and the Northern counties of Alabama. -- Publisher.